PHILOSOPHICAL AND CONSTITUTIONAL CRITIQUE OF THE NEGATIVE PUBLICATION SYSTEM IN INDONESIAN LAND REGISTRATION - Abdul Wahid; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko (Fakultas Hukum, Universitas Diponegoro, 2026)
This study analyzes Indonesia’s land registration system from a constitutional and philosophical perspective, focusing on the persistence of the negative publication system and its implications for legal certainty and social justice. By tracing the colonial genealogy of cadastral administration, the study demonstrates that land registration in Indonesia originated as a fiscal and declaratory instrument serving colonial state interests rather than as a mechanism for guaranteeing definitive land rights. This legacy continues to shape contemporary land administration, where registration records ownership claims without conferring final legal force, thereby institutionalizing systemic legal uncertainty. Using prescriptive doctrinal (normative) legal research, this study examines the 1945 Constitution, the Basic Agrarian Law (UUPA), and the regulatory framework governing land registration, supported by legal and philosophical scholarship. The analysis reveals a normative paradox within Article 19 of the UUPA: although land registration is mandated to ensure legal certainty, the negative publication system leaves land certificates perpetually vulnerable to ex post judicial annulment. As administrative decisions (beschikkingen), certificates possess formal validity but lack material finality, reducing legal certainty to conditional legality. The study further finds that the limited positive elements introduced by Government Regulation No. 24 of 1997, particularly Article 32(2), the principle of openness, and the doctrine of rechtverwerking, function only as conditional safeguards and fail to ensure legal finality in practice. From a constitutional standpoint, this system is incompatible with Articles 28D(1) and 33(3) of the 1945 Constitution and with the Pancasila principle of social justice. The novelty of this research lies in its integrated constitutional philosophical critique, which justifies reconstructing Indonesia’s land registration system toward a positive publication model as a constitutional necessity to restore legal certainty, protect citizens’ land rights, and strengthen public trust in land administration.